Environmental contaminants in biota : interpreting tissue concentrations - Beyer, W. Nelson; Meador, James Parnell, 1952- (CRC Press, 2011)
"Ecotoxicology is the study of the movement of environmental contaminants through ecosystems and their effects on plants and animals. Examining tissue residues of these contaminants in biota is basic to ecotoxicology, both for understanding the movement of contaminants within organisms and through food chains, and for understanding and quantifying injuries to organisms and their communities. This book provides guidance on interpreting tissue concentrations of environmental contaminants. "--